PENGARUH SALES PROMOTION, SHOPPING LIFESTYLE, DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING PADA PT.SENTRA PONSELINDO ITC PERMATA HIJAU - Seli Fujianti; GL. Hery Prasetya (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
This study aims to determine the effect of Sales Promotion, Shopping Lifestyle and Store Atmosphere on Impulse Buying. The type of research used in this study is a quantitative approach. The population in this study are consumers who have made purchases at the Sentra Ponsel ITC Permata Hijau shop, and the sampling technique is non-probability sampling. The data used is primary data by distributing questionnaires to 100 respondents who have visited PT. Sentra Ponselindo ITC Permata Hijau. The analytical method used is multiple regression analysis, F test, t test and the coefficient of determination. The results of the study show that simultaneously there is a significant influence between Sales Promotion, Shopping Lifestyle and Store Atmosphere on Impulse Buying. Sales Promotion partially has no significant effect on Impulse Buying. Shopping Lifestyle partially has a significant effect on Impulse Buying.